2014
DOI: 10.1088/1674-1056/23/8/083101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chirality on the thermal conductivity of single-walled carbon nanotubes

Abstract: Influence of chirality on the thermal conductivity of single-walled carbon nanotubes * Feng Ya(冯 雅) a)b) , Zhu Jie(祝 捷) a) † , and Tang Da-Wei(唐大伟) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The velocity exchanging was performed every 100 fs. [22,23] The transferred heat is calculated by the accumulation of exchanged kinetic energy as:…”
Section: Model and Methodologymentioning
confidence: 99%
“…The velocity exchanging was performed every 100 fs. [22,23] The transferred heat is calculated by the accumulation of exchanged kinetic energy as:…”
Section: Model and Methodologymentioning
confidence: 99%
“…[4] As the building blocks for various engineering applications, low-dimensional (i.e., 1D and 2D) nanomaterials have received the most extensive attention. Researchers have studied the thermal transport properties of nanowires, [5,6] single-walled or multi-walled carbon nanotube, [7,8] BN, SiC, and Ge nanotubes. [9][10][11][12][13] It is found that the carbon nanotube (CNT) has a thermal conductivity as high as ~ 3,000-3,500 W/mk at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, thermal properties associated with acoustic phonons in semiconductor nanostructures have attracted a great deal of attention. [1][2][3][4][5][6][7][8] Employing the Landauer formulation of transport theory, Rego et al [9] firstly predicted the existence of thermal conductance quantization, π 2 k 2 B T /3h, analogous to the well-known 2e 2 /h electronic conductance quantization, in the dielectric quantum wire with catenoid contacts between the wire and the reservoirs at low temperatures. This prediction has been verified by Schwab et al [10] Understanding thermal conductivity of the nanostructure is very critical to address power dissipation in a nanodevice, which is one of the important problems faced by current electronic miniaturization.…”
Section: Introductionmentioning
confidence: 99%